112 Creating a regional network for paediatric home haemodialysis. (December 2018) - Sinnott, K; Hothi, D
Abstract : Background: In 2012 we established a Paediatric Home Haemodialysis (HHD) programme in London. Nationally in the UK paediatric HHD facilities are extremely limited or non-existent and thus there is gross inequity for accessing such care. Aims: Our goal was to establish Great Ormond Street Hospital (GOSH) as a regional training centre for HHD. This provided patients from outside of our hospital access to HHD. This pathway would reduce or eliminate waiting times for HHD training and offer more children the potential benefits of HHD. Results: Collaborating with 2 other regions we developed a 'home: training' centre care pathway for Paediatric HHD. Using a standardised assessment the 'home' centre refers a suitable patient to us for HHD training. The training period is typically 4–6 weeks. The training of two carers will take place at GOSH. After discharge, these patients are monitored and supported in the community by us, the 'training' centre. The patient is then officially handed over to the 'home'centre at the first outpatient visit, one month after being home. We continue to provide expertise at quarterly outreach clinics at the 'home' centre. Conclusion: Excellent collaborative working between us and the home centres have facilitated seven (non-training centre) patients to dialyse at home. We report improved health, psychosocial and quality of life outcomes at a reduced cost. This care model did not heighten safety concerns nor did it have an adverse effect on the relationship between patients and their families with the 'home' centre. Establishing a regional training centre may accelerate the speed by which children can be transitioned to home HD without compromising on safety.